Identifikasi Clinostomum complanatum Secara Molekuler pada Ikan Air Tawar di Yogyakarta dan Riau (IDENTIFICATION OF Clinostomum Complanatum FROM FRESHWATER FISH IN YOGYAKARTA AND RIAU BASED ON MOLECULAR STUDY) - Riauwaty, Morina; ., Kurniasih; Prastowo, Joko; ., Windarti (Jurnal Veteriner, 2013)
The aim of study was, to identify Clinostomum complanatum (Digenea: Clinostomidae) infectingfreshwater fish in Yogyakarta and Riau on the bases of their molecular profiles in the internal transcribedspacer region (ITS1). Samples of climbing gouramy (Anabas testudineus) infected by Clinostomum sp. wereobtained from Kali Progo River, Yogyakarta. Whereas the climbing perch (Trichogaster trichopterus) wereobtained from the Sail River, Riau. Metacercariae of Clinostomum sp. found in the gills and visceralorgans were aseptically removed using needle, preserved in absolute ethanol. Molecular examination wasperformed by Polymerase Chain Reaction method consisted of extraction, amplification, electrophoresisand sequencing of DNA sample. The DNA sewuences of the samples were analysed by maximum parsimonyand neighbour-joining method. Phylogenetic analysis showed that Clinostomum sp. from Yogyakarta wasgenetically idential to Clinostomum complanatum, whereas Clinostomum sp. from Riau was geneticallysuspected as a new species (difference > 2%) which is included in one cluster to Clinostomum phalacrocorasis.
Keywords: Clinostomum complanatum, Philogenetic,Yogyakarta, Riau